Structural Rearrangements in Cells and Their Membranes Under Long-Term Hypothermic Storage - Repin, N. V.; Govorukha, T. P. (Problems of Cryobiology and Cryomedicine, 2005)
Morphological investigation of ultrastructure of erythrocyte membrane and liver cells, stored for a long time under 4Â°C was carried-out. It was shown, that a manifested destabilisation of their membrane structure, accompanied with spiculae formation and loss of membrane material was observed following 20 days of storage. Ultrastructural state of liver cells after 1 day of storage in a liquid phase testifies to their high integrity and reversibility in the observed changes. By lability extent under hypothermic storage the intracellular structures are graded as follows: mitochondria, endoplasmic reticulum, nuclear apparatus.